Europe and Mankind. Husserl’s Biased Reflections on the Origin of Philosophy and Not Europeanized Civilizations - Holenstein, Elmar (Investigaciones Fenomenológicas, 2021)
Nowhere does the theory-laden character of Husserl’s phenomenological intuitions become as apparent as in his reflections on cultural philosophy. It is his theory that the qualification of one‘s own tradition as one of many manifestations of something valid in itself and binding for all is a unique achievement of Greek-European philosophy. However, that conviction can be found equally in South Asian (Indian) “doctrines of Oneness” as well as in East Asian (Chinese) instances of the “Golden Rule”. Every person with a command of a natural language is capable of such an insight. The most appropriate model for individual civilizations is not the sphere metaphor, which draws on a Platonic idea of organism, the model that Husserl adopted for his conception of “home” and “foreign worlds”, but rather the image of tinkering introduced by Claude Lévi-Strauss for illiterate societies and used by François Jacob to illustrate the present biological concept of organism. Regarding cultural universals, Husserl also relies on classical ontological reflections rather than on recent biological models. The most inter-esting anthropological universals from the point of view of cultural philosophy are, however, not essential, but contingent universals. En ninguna parte el carácter cargado de teoría de las intuiciones fenomenológicas de Husserl se vuelve tan aparente como en sus reflexiones sobre la filosofía cultural. Según su teoría, la calificación de la propia tradición como una de las muchas manifestaciones de algo válido en sí mismo y vinculante para todos es un logro único de la filosofía greco-europea. Sin embargo, esa convicción se puede encontrar igualmente en las "doctrinas de la unidad" del sur de Asia (India), así como en las instancias del este asiático (chino) de la "regla de oro". Cada persona con un dominio de un lenguaje natural es capaz de tal idea. El modelo más apropiado para las civilizaciones individuales no es la metáfora de la esfera, que se basa en una idea platónica del organismo —el modelo que adoptó Husserl para su concepción de "hogar" y "mundos extranjeros"— sino la imagen de retoque introducida por Claude Lévi Strauss para las sociedades analfabetas y utilizado por François Jacob para ilustrar el concepto biológico actual del organismo. Con respecto a los universales culturales, Husserl también se basa en reflexiones ontoló-gicas clásicas más que en modelos biológicos recientes. Sin embargo, los universales antropológicos más interesantes desde el punto de vista de la filosofía cultural no son esenciales, sino universales contingentes.